Contribution to the classification study of Hymenophyllum Sm. in Vietnam - Trung, Nguyen Thanh; Hong, Pham Thi; Loc, Phan Ke (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3DO - 10.25073/2588-1140/vnunst.4648, 2017)
Abstract: Hymenophyllum Sm. is a largest genus in filmy ferns family, Hymenophyllaceae with around 250 species in the world. A long time ago, its diagnostic feature was bivalved  involucres , but in 2006, A. Ebihara et al. combined between morphology method and molecular analyses to propose a new classification of Hymenophyllaceae, therefore, its diagnostic features are rhizomes long-creeping, nearly glabrous or sparsely covered with light-coloured hairs and involucres usually bivalvate. This classification system was accepted to revise 258 collecting numbers of specimens in Vietnam. The results have claimed that Hymenophyllum genus in Vietnam comprised 10 species. Each species was provided taxonomy, distribution in Vietnam, treatment specimens and photos.